The Relationship of Knowledge Level, Home Environment and Prevention Behavior to Dengue Incidence - Maia, Crispim; de Almeida, Afonso; Gusmão, Caetano (Rifa'Institute, 2024)
Introduction: Dengue hemorrhagic fever is an infectious disease caused by dengue virus infection transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. According to health statistics and WHO data in Timor Leste reported dengue cases in 2020 from January to December 1,451 dengue cases were registered, of the total cases, 10 people died and most dengue cases came from Ermera sub-district, which was 318 cases. Objective: The purpose of this study is to determine the relationship between knowledge level, home environment and preventive behavior towards families whose members are infected with Dengue Hemorrhagic Fever in Ermera sub-district. Method: This study uses qualitative methods with the research design used is an analytical survey method with a case study approach, which describes the characteristics of the population or phenomenon being studied and is occurring, aiming to study the relationship between the independent variable and the dependent variable once and at the same time. Result and Discussion: The results showed that the level of knowledge was good (p-value 0.048) but there was a meaningful relationship between the home environment of DHF families (p-value 0.019) and the relationship of preventive behavior (p-value 0.000) to the incidence of DHF. Conclusion: From the results of the study above, it can be concluded that there is an influence of the family home environment and preventive behavior with the incidence of DHF